Impact of ICT adoption on the food security of agricultural households in Burkina Faso - Ibrahim SANA; Achille Augustin DIENDERE; Jacob Afouda YABI (Theoretical and Applied Economics)

(untitled)
This research evaluates the impact of the adoption of information and communication technologies (ICT) on the food security of farming households in Burkina Faso. Data were collected from 420 farmers in the Centre region, selected by simple random sampling. Descriptive statistics and the propensity score matching (PSM) model were used. The results reveal that farm households that adopt ICTs benefit from a substantial improvement in their food security, reflected by an average treatment effect (ATE) of 0.505. These results imply that targeted policies to promote ICT are needed in the agricultural sector to improve food security in rural areas.